2015
DOI: 10.1039/c5ra10407f
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a P(THF-co-PO)-b-PB-b-P(THF-co-PO) triblock copolymer via cationic ring-opening polymerization and its use as a thermoset polymer

Abstract: The triblock copolymer poly(tetrahydrofuran-co-propylene oxide)-b-polybutadiene-b-poly(tetrahydrofuran-co-propylene oxide) [P(THF-co-PO)-b-PB-b-P(THF-co-PO)] was synthesized via the cationic ring-opening copolymerization of tetrahydrofuran (THF) and propylene oxide (PO) in the presence of hydroxyl-terminated polybutadiene (HTPB). The copolymerization mechanism was studied using Fourier transform infrared spectroscopy (FT-IR), nuclear magnetic resonance (NMR), and size-exclusion chromatography coupled with mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…These results indicated that poly(THF) formation required an epoxide as a comonomer, a relatively common occurrence for THF polymerization. [42,43,59,60] To avoid gelation, we next explored CHO/THF copolymerization reactions in CH 2 Cl 2 (Table 1, Table S1). A reaction run with an excess of CHO consumed both monomers efficiently (solid lines, Figure 1), and resulted in a moderate molecular weight polyether (M n = Table 1: Molecular weight and composition of THF/CHO copolymers synthesized with various feed ratios, solvents, and concentrations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results indicated that poly(THF) formation required an epoxide as a comonomer, a relatively common occurrence for THF polymerization. [42,43,59,60] To avoid gelation, we next explored CHO/THF copolymerization reactions in CH 2 Cl 2 (Table 1, Table S1). A reaction run with an excess of CHO consumed both monomers efficiently (solid lines, Figure 1), and resulted in a moderate molecular weight polyether (M n = Table 1: Molecular weight and composition of THF/CHO copolymers synthesized with various feed ratios, solvents, and concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…We identified poly(tetrahydrofuran) (poly(THF)) as a potentially useful mid-block for a TPE because it is a flexible polyether with high abrasion resistance. [42][43][44][45][46] It has a glass-transition temperature (T g ) of À 83 °C, [47] making it a useful soft block in segmented polyurethane TPEs like Spandex. [48] While it has a T m of 41 °C, not ideal for a TPE soft block, we envisioned that the crystallinity could be largely disrupted by incorporating a small amount of a comonomer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polytetrahydrofuran, with a large number of polar ether bonds, has good cryogenic properties and it is also used to prepared copolymers in order to improve mechanical properties. A novel triblock copolymer poly(tetrahydrofuran-copropylene oxide)-b-polybutadiene-b-poly(tetrahydrofuran-co-propylene oxide) [P(THF-co-PO)-b-PB-b-P(THF-co-PO)] was reported by Fan et al [133,134]. P(THF-co-PO)-b-PB-b-P(THF-co-PO) was synthesized by covalently attaching copolyether segments onto the terminals of HTPB via cationic ring-opening copolymerization of THF and propylene oxide (PO) in the presence of HTPB as a macroinitiator and BF 3 •OEt 2 .…”
Section: Other Modificationsmentioning
confidence: 99%
“…1,2 Recently, an important development was reported of the application of HTPB in the eld of solid rocket propellants. [3][4][5][6][7][8][9][10][11][12] Usually, three different segment structures in the HTPB backbone are detected; they are cis-1,4 unit, trans-1,4 unit and 1,2 unit as shown in Scheme 1. Due to these structures, different physical and mechanical properties can be observed.…”
Section: Introductionmentioning
confidence: 99%